Language Style and Language Function Of HKBP Preacher in Sunday Sermon Service and GBI Preacher in Sunday Sermon Service - Tanjung, Nikho_Sanjaya (The Explora, 2022)
This research is entitled “ Language Function and Style. The source of data this research is script of “HKBP and GBI Sermon” this research uses descriptive qualitative which explores and understand themeaning the meaning of individuals or group. This research is to apply Michael Halliday in LanguageFunction and Martin Joos theory of Language Style. People who speak the same tongue may use differentstyle to transfer their information and Communication. There are Seven categories of Language Functionsuch as instrumental function, regulartory function, interactional function, personal function, heuristicfunction, imaginative function and there are five categories in language style such as intimate style,casual style, consultative style, formal style, and frozen style. There are 3 videos HKBP consists 6instrumental function, 0 regulartory function, 4 interactional function, 5 personal function, 8 heuristicfunction, 1 imaginative function, 28 representational function. As three videos of GBI Sermon as thedata result of the analysis, they are 13 instrumental function, 0 regulartory function, 29 interactionalfunction, 4 personal function, 10 heuristic function, 2 imaginative function and 28 representationalfunction. As three videos of HKBP sermon in Language Style consists 0 intimate style, 19 casual style,3 consultative style, 40 formal style, and 1 frozen style. It is concluded on language function, HKBPsermon is dominantly in using interactional function and representational function and while GBIsermon is dominantly in using interactional language and representational function. Based on theLanguage Style, HKBP sermon is dominantly in using formal style and casual style, and GBI sermon issame with HKBP. Since sermon is giving information of religion and word of God, the preacher mostlyused formal style while in language function for representational is dominantly used because in a sermonmostly the preacher explains and make some clarification for the word of God.